Benefits of yeast culture supplementation in diets for horses - Taylor-Pickard, Jules Anne; Stevenson, Z (MTT, 2008)
Feeding strategies for performance horses using mainly high starch diets, can result in enhanced susceptibility to colic or laminitis (Kronfeld and Harris, 1997). The incidence of which can be reduced through the use of beneficial microbial supplement that increase nutrient availability, modify gut microflora and enhance performance. One source is a live culture of the yeast Saccharomyces cerevisae (Yea-Sacc®1026; CBS 493.94, Alltech Inc, USA). The addition of Saccharomyces cerevisiae limits the extent of undesirable changes in the intestinal ecosystem of the horse. It can improve the microbial balance in the hindgut of horses, stimulating the population of fibre digesting bacteria and their activity. Such yeast cultures have also been found to increase the digestibility of dietary nutrients, particularly ADF due to its positive effect on the number and activity of cellulolytic bacteria. In the case of high starch diets, where there may be a negative digestive interaction between starch and cellulose which can lead to digestive disorders, supplementation with yeast culture might limit the effect by rebalancing the complex microbial population of the hind gut yeast cultures. In improving fibre digestibility, supplementation with a yeast culture would increase nutrients supply, namely of energy and nitrogen to some extend and as a result the performance of horses: lactating mare, foals and yearling. In conclusion, increasing number of studies have shown that supplementation with a yeast culture significantly improves the digestibility of fibre within the diets and goes some way to counteracting the negative effects of diets containing high levels of starch.
Keywords: Ko; horse; starch diet; yeast; digestion; performance